O Método fenomenológico nas práticas das psicoterapias fenomenológicas, humanistas e existenciais: modalidades e tendências - Schievano, Bruna Alves (2022)
This study was divided into three chapters, whose central axis is the search for understanding how Humanistic, Phenomenological and Existential Psychotherapies have dealt with the phenomenological method in relation to qualitative research in Psychology and clinical practice, aiming to find out how they proceed, what are the modalities and trends. For this, in chapters I and II, narrative reviews were carried out that presented a brief history of Psychotherapy, whose main objective was to provide a base historical context and theoretical consistency to the following studies. In Chapter II, the focus was on the emergence and early developments of humanistic, phenomenological and existential psychotherapies. The realization of the “Third force” movement is highlighted, in addition to the socio-political and cultural context sensitive to the reception of Humanistic Psychology. At that time, Philosophical Phenomenology (Husserl and Heidegger) and Existentialism were assumed as theoretical and methodological resources in psychopathological investigations and psychotherapeutic practices developed by this new approach: Humanistic Psychology. However, as the study pointed out, these appropriations were carried out superficially, generically and more explicitly a posteriori by other collaborators. In Chapter III, a qualitative systematic review of the literature was carried out, in search of the main objective of this study. Articles in Portuguese, complete and referring to the period from 2011 to 2021, were selected from searches in the LILACS, PePSIC and SciELO-Brasil databases. As keywords were used: (phenomenological method) AND (clinical OR psychotherapy). The localized references were selected according to established inclusion criteria, and the corpus consisted of 45 articles, which were quantitatively analyzed (Distribution of published articles; Performance of Brazilian journals; Rank of psychologists with the highest publication rate; Institutional affiliations of authors and co-authors) and qualitatively according to the dimensions: (I) methodological design employed, (II) data analysis, (III) description of the phenomenological method, (IV) phenomenological method in therapeutic practice. The results indicate: greater production of articles in 2020; concentration of publications in a humanistic journal; predominance of authors and universities from Ceará and predominance of empirical productions. The most used instrument for data collection is the semi-structured interview; for data analysis, much was used to the one proposed by Giorgi and Sousa, however the most cited analysis method in the researches was the existential-hermeneutic phenomenological one, which was based on different authors and philosophers. The philosophical concepts proposed by Husserl appear in the psychotherapeutic practice of psychologists in a different way from that explored as described and detailed by Husserl, conceiving it as a (professional) posture, an attitude of understanding taken by the psychologist, thus evidencing his way of of intervention. Still, it is perceived the lack of a distinction between the specificities and objectives of the method, since the authors treat as synonyms the ideas of epoché, reduction, phenomenological reduction, with a general meaning of attitude, a posture of finding the client/patient without prejudices. Thus, it seems incoherent to apply the phenomenological method in the practice of Psychotherapy, directly as a psychotherapeutic resource, in view of its elaboration and development as a method of investigation and validation of phenomena, a particularly introspective, rational and reflective task.